A Statistical Study of the Productivity of Labour in Some Syrian Textile Companies Between 1994 – 2004 (Latakia University Journal - Economic and Legal Sciences Series, 2024)
Labour represents an active element in the productivity operation and a strong supporter for both the economical and social development through many ages. Labour means human physical and mental activity that aims to fulfill financial interest, and to accomplish a high amount of social and cultural services to establish a definite purpose during limited time. So, the human element of working is the most important one in production. And human investments are greater than that of other elements. In this context, the research has been done to face problems that interrupt workers'activity, because their behaviour are affected by their hopes, desires and motives.Unlike other production elements that may be managed according to our needs, and because of the great role of by the Syrian textile sector in supporting the national economy and offering the budget huge resources, this thing affects directly the worker's productivity and performance rate.In this study we analyzed the workers' productivity of some Syrian textile companies by analyzing contrasts and differences between them. The results which have been reached are as follows:• 1- There are substantial differences among workers, productivity average through studies o several companies.• 2- There are basic disparities among workers productivity average between each two companies: (Cotton Company - United Commercial and Industrial Company), (Cotton Company - Textile Company), (Cotton Company - AL Walid Company).• 3- There are no substantial differences among workers, productivity average between each two companies: (United Commercial and Industrial (Company - Syrian Company), (United Commercial and Industrial company - Textile company of Jablah), (Syrian company - textile company of Jablah).